HUBUNGAN PENGETAHUAN LANSIA TENTANG ARTRITIS RHEUMATOID DENGAN UPAYA PENATALAKSANAANNYA - Nugroho, Christianto (Jurnal AKP, 2014)
United Nation Of Health Agency or World Health Organization ( WHO ) establishes 65 years as the age that shows the aging process takes place in a real and someone has called the elderly. One of the rheumatic group that often accompany old age is Rheumatoid Arthritis ( Fitriany , 2009). In Indonesia, the incidence  of  Rheumatoid Arthritis in the elderly has increased. Though this disease can be treated if the elderly have a good knowledge. The purpose of this study was to determine the relationship between knowledge with management efforts of Rheumatoid Arthritis at Badas Public Health Centers Kediri Regency .Research design used in study was the Analitic Cross Sectional.  Population in this study were all elderly with Rheumatoid Arthritis. The size was 30 elderly. Sampling technique using purposive sampling with a sample of 15 elderly. Instrument of the research using a questionnaire to measure knowledge and knowledge management using a questionnaire to measure management efforts. The place of research in the Badas Public Health Centers Kediri Regency. Analysis of the data used is Descriptive Analytics .  Results of the research in this study showed the majority of respondents have less knowledge, less salvage as much as 7 respondents ( 46.7 % ). So it can be concluded that there was relationship between knowledge with management efforts of Rheumatoid Arthritis at Badas Public Health Centers Kediri regency Researcher concluded the relationship between knowledge with management efforts of Rheumatoid Arthritis in the elderly due to age, education, gender, occupation, and experience. Thus the role of health educators is very important, the cooperation of all parties also contribute in improving the quality of life of the elderly. Ranging from health centers, neighborhood health center, club elderly or in a hospital. And the runners are expected to participate actively and independently in each extension activities mainly on the management of Rheumatoid Arthritis . Keywords: knowledge, management efforts, and elderly